Kosakata KBBI: Jembatan Linguistik atau Batas Sosial dalam Penerimaan Komunitas LGBT Di Indonesia - Rahmin Meilani Putri; Satriani Satriani; Rinda Widya Ikomah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The issue of LGBT (Lesbian, Gay, Bisexual, and Transgender) remains a subject of controversy. In Indonesia, the presence of the LGBT community has sparked a backlash from various quarters. However, LGBT concepts and terms are included in the Kamus Besar Bahasa Indonesia (KBBI). The inclusion of this LGBT-related vocabulary in the KBBI presents a contradiction. This is because words symbolize a thought (concept/idea), so the inclusion of these terms indicates acceptance of the LGBT concept in Indonesia. Furthermore, language reflects the society of its speakers. This study aims to identify a number of LGBT-related terms in the KBBI and to examine their relevance to the acceptance of LGBT people in Indonesia. The research method used is qualitative analysis with an anthropological approach. The data used consists of terms related to LGBT issues in the KBBI. The results of this study indicate that several terms related to LGBT appear in the KBBI. Furthermore, the inclusion of these terms serves as an open indicator of the linguistic acceptance of LGBT in Indonesia